The Need for Economic Empowerment Programs for Refugees in Kampala Urban Refugees Settlement in Uganda to Realize their Economic Rights - M.K Mukisa Angello (Uganda Christian University, 2024)
This thesis asserts that there is need for more economic empowerment programs in Uganda for refugees to realize their economic rights. Refugees in Uganda should be looked at as an asset rather than a liability and it is through these economic empowerment programs refugees realize their economic rights as they take part in the economic empowerment programs and also it is to the benefit of host communities. Above all the Uganda's legal framework should be applauded for it has acted as an inspiration to many countries.